Pornografi dan Pornoaksi Persfektif Hukum Islam - Shohibul Adib (LPPM IAIN Sorong, 2019)
The progress of science and technology that can not be avoided, print and electronic media and the potential to contribute greatly to the spread of the problem and pornoaksi and pornografi. The results of this study show three subjects. First, in the 16th century, the roots of pornography in the Western world is considered as a balance between the political and sexual. Pornography share the progress with the development of civilization and modern technology. Second, the discussion of the perspective of Islamic law against pornography use two approaches, namely the normative and juridical approach. From the normative refers to the two main sources of Islam, namely the Qur'an and Sunnah to see the Quranic verses and hadiths of the Prophet related to pornography. While the juridical explanation will refer to the MUI fatwa and the Law of the Republic of Indonesia No. 44 2008 on pornography. Third, pornography and porno-action perspective of Islamic law are forbidden, it is clearly a normative based on several verses in the Qur'an. And some of the traditions of the Holy Prophet are strictly prohibited.